2009
DOI: 10.1016/j.neurobiolaging.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Modification upon aging of the density of presynaptic modulation systems in the hippocampus

Abstract: Please cite this article in press as: Canas, P.M., et al., Modification upon aging of the density of presynaptic modulation systems in the hippocampus, Neurobiol Aging (2008) Abstract Different presynaptic neuromodulation systems have been explored as possible targets to manage neurodegenerative diseases. However, most studies used young adult animals whereas neurodegenerative diseases are prevalent in the elderly. Thus, we now explored by Western blot analysis how the density of different presynaptic markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
72
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 52 publications
19
72
3
3
Order By: Relevance
“…In line with this, age-dependent reduction in the density of synaptic proteins were reported in the rodent brain, namely SNARE complex proteins, vesicle-mobilizing proteins, vesicular neurotransmitter transporters, postsynaptic proteins, and components of the synaptic vesicle cycle (Canas et al, 2009;VanGuilder et al, 2010), which can contribute to the hippocampal function decline and thus to reduction of memory performance (Allard et al, 2012;Gage et al, 1984a;Kennard and Woodruff-Pak, 2011;Pistell et al, 2012).…”
Section: Discussionsupporting
confidence: 53%
“…In line with this, age-dependent reduction in the density of synaptic proteins were reported in the rodent brain, namely SNARE complex proteins, vesicle-mobilizing proteins, vesicular neurotransmitter transporters, postsynaptic proteins, and components of the synaptic vesicle cycle (Canas et al, 2009;VanGuilder et al, 2010), which can contribute to the hippocampal function decline and thus to reduction of memory performance (Allard et al, 2012;Gage et al, 1984a;Kennard and Woodruff-Pak, 2011;Pistell et al, 2012).…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, we failed to identify diabetes-induced neuronal loss in brain sections stained either cresyl violet or FluoroJade-C, which was corroborated by the lack of altered microtubuleassociated protein 2 (MAP2) immunoreactivity, a marker of neuronal density [95]. This indicates that T2D primarily causes synaptic deterioration without neuronal death, which resembles the events occurring in aging [128] and models mimicking early AD [129,130], thus corroborating the association of insulin resistance and T2D with increased incidence of AD. Moreover, compared to non-diabetic Wistar rats, also non-obese insulin-resistant Goto-Kakizyki (GK) rats displayed reduced spatial memory, which was accompanied by reduced pre-synaptic markers and increased glial specific proteins in the hippocampus [131].…”
Section: Insulin-resistant Diabetesmentioning
confidence: 56%
“…A similar decrease in both CB1 receptor binding and mRNA levels was found in most of the basal ganglia in rats during ageing [223]. Also, in isolated rat hippocampal synaptosomes, a reduction in CB1 receptor densities in ageing was described [224]. On the contrary, Liu et al [225] found no differences in CB1 receptor protein levels between four-and 24-month-old rats in the hippocampus.…”
Section: Cannabinoid System May Change During Ageing In the Brainmentioning
confidence: 67%